Modeling, Diagnostics and Process Control Implementation in the DiaSter System - Korbicz, Józef; Koscielny, Jan M. (Springer Berlin Heidelberg : Imprint: Springer, 2011)
Modern control systems are complex in the sense of implementing numerous functions, such as process variable processing, digital control, process monitoring and alarm indication, graphic visualization of process running, or data exchange with other systems or databases. This book conveys a description of the developed DiaSter system as well as characteristics of advanced original methods of modeling, knowledge discovery, simulator construction, process diagnosis, as well as predictive and supervision control applied in the system. The system allows early recognition of abnormal states of industrial processes along with faults or malfunctions of actuators as well as technological and measuring units. The universality of solutions implemented in DiaSter facilitates its broad application, for example, in the power, chemical, pharmaceutical, metallurgical and food industries. The system is a world-scale unique solution, and due to its open architecture it can be connected practically with any other control systems. The monograph presents theoretical and practical results of research into fault diagnosis and control conducted over many years within the cooperation of Polish research teams from the Warsaw University of Technology, the University of Zielona Góra, the Silesian University of Technology in Gliwice, and the Technical University of Rzeszów.             The book will be of great interest to researchers and advanced students in automatic control, technical diagnostics and computer engineering, and to engineers tasked with the development of advanced control systems of complex industrial processes.